KONSENTRASI DAN MOTILITAS SPERMATOZOA CAUDA EPIDIDIMIS BANDIKUT (Echymipera kalubu): SPERM CONCENTRATIONAND MOTILITYOF CAUDA EPIDIDYMIS BANDIKUT (Echymipera kalubu) - Angelina Novita Tethool; Raden Iis Arifiantini; Srihadi Agungpriyono (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2012)
One of the factorthat influencethe process offertilization on Echymiperakalubu is the quality of the spermwhich produced by males. The ability of spermtofertilize anovumis not only owned by the spermatozoa which derived from the results of ejaculation, butis also owned by spermatozoa from the caudaepididymis.This study aimed to determine sperm concentration and motility from caudaepididymis.Twenty-one males E. kalubuwere used which was 370-1500g. Based onthis weight, it was divided into three groupings, they were prepubertal (370-640 g), young adult (>640-850g) and adult (>850g).The results showed that the sperm concentration of the prepubertal was1.75±1.14x106/ml,the young adult was 8.86±4.21x106/ml and increased to12.56±6.33x106/mlin the adult group.Sperm motility also increased with increasing maturity. The prepuberta lgroup showed that sperm motility was33.33±25.17%, increased to41.67±12.58% (young adult) and3.54±57.50% followed by the adult.